Diagnosis and management of childhood aplastic anaemia. Issue 8 (August 2015) - Bhatnagar, Neha; Samarasinghe, Sujith
Abstract: Aplastic anaemia is a rare disorder in children. ∼20% of cases are inherited, whilst the rest are considered as acquired or idiopathic where no cause can be found. Diagnosis of the inherited causes of aplastic anaemia can be challenging but it is important for appropriate management and counselling. For idiopathic severe aplastic anaemia, a matched sibling donor haematopoietic stem cell transplant is the treatment of choice. If a matched sibling donor is not available, the options include immunosuppressive therapy with horse ATG and ciclosporin or unrelated donor haematopoietic stem cell transplant. Immunosuppressive therapy with horse anti-thymocyte globulin (ATG) is superior to rabbit ATG. Outcomes following matched unrelated donor haematopoietic stem cell transplantation are now similar to that of matched sibling donor haematopoietic stem cell transplant. The decision to proceed with immunosuppressive with ATG or unrelated donor stem cell transplant will depend on the likelihood of finding a matched unrelated donor and the differing risks and benefits that each therapy provides.